A Finite Element Analysis of Lateral Buckling of Tensile Armor Layers of Flexible Pipes Considering Machining Geometry Defects - Yongyu Li; Qingzhen Lu; Xiufeng Yue; Hailong Lu; Qianjin Yue; Yangcheng Lu (Journal of Marine Science and Engineering)
The tensile armor layer plays a crucial role in offshore flexible pipelines, primarily bearing axial tensile loads. However, during installation and operation, it may experience compressive forces, leading to a risk of lateral buckling, which is further intensified by manufacturing deviations in the steel strips. This study introduces a method to quantify these deviations based on the circumferential length change in defect segments in helically wound steel strips. A deviation model is established and analyzed using Abaqus finite element simulations to evaluate the impact of helical angles and deviation severity on the critical lateral buckling load. The results reveal that as the deviation severity increases, the critical buckling load significantly decreases, with reductions of up to 65% for small helical angles. Additionally, the rapid rise in bending moment at the defect location is identified as the primary cause of lateral buckling initiation.